Application of cost-benefit and break-even analysis for the development of stingless bees farming in Malaysia - Abdurofi, Ilmas; Ismail, Mohd Mansor; Ismail, Normaz Wana; Abdullah, Amin Mahir (Universiti Malaysia Sarawak, 2021)
The information about the economic and financial aspects of stingless bees farming is still limited along with some issues of high selling price and expenses. Therefore, the study initially aims to describe comprehensively cost-benefit, and break-even analysis of stingless bees farming in Malaysia. The study uses primary data and employs about 124 stingless beekeepers in all regions in Malaysia as number observation. The sampling method uses non-probability sampling, while the costing analysis, net return, input-output ratio, cost-benefit ratio and breakeven analysis are applied as analytical techniques. As a result, the stingless bees farming may generate considerable earnings, mainly in the area of Peninsular Malaysia, whilst the Sarawak region shows efficient cost of production in the break-even point. Furthermore, labor expense constitutes a predominant concern in the production and hive investment is required as high capital expenditure. The study recommended that the government and beekeepers should find alternative hive systems in order to reduce cost and focus on the massive production of stingless honey bees in the Sarawak area, while Peninsular Malaysia may turn into a main concentration of trading and marketing honey products.